Agama Dan Kesehatan Mental - Matnur Ritonga (ISLAMICA, 2017)
Humans are essentially born in a state of fitrah (holy, clean, straight, and mentally healthy). A man with two main tasks, namely: as' Abdun (servant of God), also as Caliph (Ruler of theearth). So Allah SWT install on human things ranging from hardware (al-hawas al-khams and other members of jasadiyah) and software (al-ruh, al-'aql, al-nafs, al-qalb) as a means to carry out the two mandates. Selected human beings are inspired even karomah. Those who are able to use all the grace will be mentally healthy, through the process: learning (iqro: qur'aniyah verses & verses kauniyah), will produce: faith, islam, and ihsan. Are those who do not want to explore the potential within him will be mentally ill if the category: nifaq even kufr. Those who are sick mentally will never know and realize that they are sick. It is obtained from the Mafhun mukhalafah in a hadith it is said: "Health is the crown used by healthy people. Only those who are sick are able to see it, "this is a heavy sarcasm so that we do not belong to the sick, either: his zahiriyah or his bathinyah. Bring them to a teacher and doctor. Summary of the wisdom of Imam Syafi'i's words: "Truly teachers and doctors are two people who are able to heal the sick (soul and body), they will not give the medicine if they are not glorified (visited). So be prepared to continue in a state of stupid (ill) and sick (soul) if you do not want to get close / come to both. "Prophet Muhammad is a Mu'allim and also Thabib.'lama is the greatest medicine to nourish this nation. There is no other way except this generation should give birth 'Ulama who is a doctor or a doctor who is also' Ulama.